Living Donor Kidney Transplantation: Global and Regional Trend - Nadjafi-Semnani, Mohammad; Simforoosh, Nasser; Nadjafi-Semnani, Ali (Urology Journal, 2021)
Request for kidney transplantation (K.T.) is increasing rapidly because of the worldwide pandemic of end-stage renal disease, and the most critical issue is organ shortage. The available deceased donors will not resolve the continuing scarcity of organs. It is now professionally and ethically acknowledged and is vital to pay money to the donors for excluding disincentives of living organ donation. Living organ donation should be a vital part of the K.T. Program of any country.